The mental health of elite-level coaches: A systematic scoping review - Frost, J.; Walton, C. C.; Purcell, R.; Fisher, K.; Gwyther, K.; Kocherginsky, M.; Rice, S: M. (Sports Medicine - Open, 2024)
Background Elite-level coaches are exposed to multiple performance, organisational and personal stressors which may contribute to reduced mental health and wellbeing. This systematic scoping review examined the current body of evidence to explore what is known about the mental health of elite-level coaches (i.e. wellbeing and mental ill-health), the risk and protective factors that influence coach mental health, and the relationship between mental health and coaching effectiveness.